Env diversity-dependent protection of the attenuated equine infectious anaemia virus vaccine. Issue 1 (1st January 2020) - Lin, Yuezhi; Wang, Xue-Feng; Wang, Yuhong; Du, Cheng; Ren, Huiling; Liu, Cong; Zhu, Dantong; Chen, Jie; Na, Lei; Liu, Diqiu; Yang, Zhibiao; Wang, Xiaojun
ABSTRACT: Lentiviruses harbour high genetic variability for efficient evasion from host immunity. An attenuated equine infectious anaemia (EIA) vaccine was developed decades ago in China and presented remarkably robust protection against EIA. The vaccine was recently proven to have high genomic diversity, particular in env . However, how and to what extent the high env diversity relates to immune protection remains unclear. In this study, we compared immune protections and responses of three groups of horses stimulated by the high-diversity vaccine EIAV_HD, a single molecular clone of the vaccine EIAV_LD with low env diversity, as well as a constructed vaccine strain EIAV_MD with moderate env diversity. The disparity of virus-host interactions between three env diversity-varied groups (5 horses in each group) was evaluated using clinical manifestation, pathological scores, and env -specific antibody. We found the highest titres of env antibodies (Abs) or neutralizing Abs (nAbs) in the EIAV_HD group, followed by the EIAV_MD group, and the lowest titres in the EIAV_LD group ( P <0.05). The occurrence of disease/death was different between EIAV_HD group (1/0), EIAV_MD (2/2), and EIAV_LD group (4/2). A similar env diversity-related linear relationship was observed in the clinical manifestations and pathological changes. This diversity-dependent disparity in changes between the three groups was more distinct after immunosuppression, suggesting that env diversity plays an important role in protection under low host immunocompetence. In summary, inoculation with vaccines with higher genetic diversity could present broader and more efficient protection. Our findings strongly suggest that an abundance of Env antigens are required for efficient protection against lentiviruses.